Age alters the oncogenic trajectory toward luminal mammary tumors that activate unfolded proteins responses. Issue 10 (15th September 2022) - Jenkins, Edmund Charles; Chattopadhyay, Mrittika; Gomez, Maria; Torre, Denis; Ma'ayan, Avi; Torres‐Martin, Miguel; Sia, Daniela; Germain, Doris
Abstract: A major limitation in the use of mouse models in breast cancer research is that most mice develop estrogen receptor‐alpha (ERα)‐negative mammary tumors, while in humans, the majority of breast cancers are ERα‐positive. Therefore, developing mouse models that best mimic the disease in humans is of fundamental need. Here, using an inducible MMTV‐rtTA/TetO‐NeuNT mouse model, we show that despite being driven by the same oncogene, mammary tumors in young mice are ERα‐negative, while they are ERα‐positive in aged mice. To further elucidate the mechanisms for this observation, we performed RNAseq analysis and identified genes that are uniquely expressed in aged female‐derived mammary tumors. We found these genes to be involved in the activation of the ERα axis of the mitochondrial UPR and the ERα‐mediated regulation of XBP‐1s, a gene involved in the endoplasmic reticulum UPR. Collectively, our results indicate that aging alters the oncogenic trajectory towards the ERα‐positive subtype of breast cancers, and that mammary tumors in aged mice are characterized by the upregulation of multiple UPR stress responses regulated by the ERα. Abstract : Older women tend to develop estrogen receptor‐alpha (ER󠆴α)‐positive breast cancers, despite having lower levels of estrogen, but this fundamental observation has never been recapitulated in mice, where most studies are performed in young mice. We show that the expression of the same oncogene in the mammary glands of young and aged mice leads to ER󠆴α‐negative and ER󠆴α‐positive, respectively. Tumors in aged mice are characterized by the activation of multiple unfolded protein responses (UPR) driven by the ER󠆴α that is not found in ER󠆴α‐positive cells from young mice. These findings suggest that age dictates not only breast cancer subtypes but also ER󠆴α transcriptional programs.